2021
DOI: 10.1159/000513948
|View full text |Cite
|
Sign up to set email alerts
|

Community- and Hospital-Acquired Acute Kidney Injury in COVID-19: Different Phenotypes and Dismal Prognosis

Abstract: Introduction: Acute kidney injury (AKI) is common in coronavirus disease 2019 (COVID-19). It is unknown if hospital-acquired AKI (HA-AKI) and community-acquired AKI (CA-AKI) convey a distinct prognosis. Methods: The study aim was to evaluate the incidence and risk factors associated with both CA-AKI and HA-AKI. Consecutive patients hospitalized at a reference center for COVID-19 were included in this prospective cohort study. Results: We registered 349 (30%) AKI episodes in 1,170 hospitalized patients, 224 (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 45 publications
(63 reference statements)
5
30
0
8
Order By: Relevance
“…Almost two thirds of our patients presented with AKI at the moment of admission, most of them being known with a history of CKD. Numerous studies report that AKI at admission is frequent in COVID-19 (34)(35)(36), but, regarding prevalence of previous CKD, some authors found it higher in AKI at admission (34,37) similar to our study, whereas others in hospital-developed AKI (38). This difference was probably due to the modality of admission in the hospital, availability and extension of ICU departments in different hospitals, type of treatment available and recommended by evolving guidelines in the last year of the pandemic.…”
Section: Impact Of Covid-19-specific Treatment and Severity Of Akisupporting
confidence: 77%
See 1 more Smart Citation
“…Almost two thirds of our patients presented with AKI at the moment of admission, most of them being known with a history of CKD. Numerous studies report that AKI at admission is frequent in COVID-19 (34)(35)(36), but, regarding prevalence of previous CKD, some authors found it higher in AKI at admission (34,37) similar to our study, whereas others in hospital-developed AKI (38). This difference was probably due to the modality of admission in the hospital, availability and extension of ICU departments in different hospitals, type of treatment available and recommended by evolving guidelines in the last year of the pandemic.…”
Section: Impact Of Covid-19-specific Treatment and Severity Of Akisupporting
confidence: 77%
“…We found no differences between AKI at admission and hospital-acquired AKI regarding age or comorbid burden. Most authors report age and multiple comorbidities as predictive factors for AKI at admission (34,37) and few found advanced age to be associated with hospital-acquired AKI (38).…”
Section: Impact Of Covid-19-specific Treatment and Severity Of Akimentioning
confidence: 99%
“…After reviewing the full texts of 938 articles, 71 COVID-19 studies were included in the meta-analysis ( Figure 1A ). 1 - 3 , 13 , 27 …”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] The rate of AKI in patients with COVID-19 is extremely variable across countries and may differently affect patients with similar disease severity. [5] In a large cohort of vulnerable patients in the USA, the incidence of AKI approached 60%. [6] In Europe, few studies have reported information on AKI in the general population.…”
Section: Introductionmentioning
confidence: 99%